THE EFFECTIVENESS OF STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) IN TEACHING READING COMPREHENSION OF THE FIRST SEMESTER STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Yusniasri Primasari (JARES (Journal of Academic Research and Sciences), 2018)
Strategy plays the important role to make students understand reading materials. Teachers should be able to choose right teaching strategy in order to make the students interested more in learning beacause they enjoy learning and reading the given material. This study was conducted to find out whether the use of STAD in teaching of reading comprehension is effective to improve the student reading comprehension achievement. The design of the study was experimental reasearch. The study was conducted in Islamic University of Balitar. the researcher takes one class of the first semester students of english language education study program in the islamic university of balitar blitar in the academic year 2016/2017. and in analyzing the data, the researcher used the statistical procedures namely dependent T-test. The finding of this study is the score that students got after treatment increased. It means that the hypothesis alternative is accepted and the null hypothesis is rejected. By those facts, Ho hypothesis is rejected and H1 hypothesis is accepted. Thus, it can be concluded that using STAD method in teaching reading comprehension proved to be effective in increasing teh students ’ reading comprehension achievement.